Investigating the Relationship between Metalinguistic Knowledge and L2 Writing Among Intermediate-level Adult Turkish EFL Learners - Aydin, Fatma (Issues in Language Studies, 2019)
The present study investigates the nature of metalinguistic knowledge among intermediate-level adult Turkish EFL learners, and the relationship between their metalinguistic knowledge and L2 writing in terms of complexity, accuracy and fluency. The participants of the present study are a total of 78 intermediate-level adult Turkish EFL learners. The data collection instruments of the present study include Oxford Quick Placement Test (OQPT), Productive Metalinguistic Knowledge Test (PMKT), Receptive Metalinguistic Knowledge Test (RMKT) (adapted from Ellis, 2009) and opinion essays of a smaller group of the participants. The results revealed that intermediate-level adult Turkish EFL learners have moderate to high productive and metalinguistic knowledge. They are better at explaining why a L2 sentence is grammatically incorrect than referring to the exact grammar rule and using technical words for the grammatical features. The results also revealed that there is significant moderate correlation between metalinguistic knowledge and writing accuracy.